2017
DOI: 10.14202/vetworld.2017.702-710
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline resistance phenotypes and genotypes of coagulase-negative staphylococcal isolates from bubaline mastitis in Egypt

Abstract: Aim::This study was devoted to elucidate the tetracycline resistance of coagulase-negative staphylococci (CNS) derived from normal and subclinical mastitic (SCM) buffaloes’ milk in Egypt.Materials and Methods: ::A total of 81 milk samples from 46 normal buffalo milk samples and 35 SCM buffalo milk samples at private dairy farms of Egypt were used in this study. CNS were identified using phenotypic and molecular methods (polymerase chain reaction [PCR]). CNS isolates were tested for tetracycline resistance usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
11
3
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
8
11
3
1
Order By: Relevance
“…TET resistance is usually conferred by the acquisition of tet (M), tet (O), and tet (S), which encode ribosomal protection proteins, or tet (K) and tet (L), which encode efflux pumps [ 34 ]. Similar to previous publications [ 26 , 46 ], all of the TET-resistant CoNS including S. saprophyticus , S. sciuri , S. simulans , and S. lentus possessed tet (K). In contrast to the TET-resistant CoNS, all the S. chromogenes and S .…”
Section: Discussionsupporting
confidence: 87%
“…TET resistance is usually conferred by the acquisition of tet (M), tet (O), and tet (S), which encode ribosomal protection proteins, or tet (K) and tet (L), which encode efflux pumps [ 34 ]. Similar to previous publications [ 26 , 46 ], all of the TET-resistant CoNS including S. saprophyticus , S. sciuri , S. simulans , and S. lentus possessed tet (K). In contrast to the TET-resistant CoNS, all the S. chromogenes and S .…”
Section: Discussionsupporting
confidence: 87%
“…Regarding tetracycline, most S. aureus isolates (32/35) were susceptible, while nonsusceptible isolates belonged to the following CNS species: S. caprae (4), S. haemolyticus (3), S. lentus (2), S. capitis (1), S. hominis (2), S. rostri (1), and S. warneri (1). Tetracycline has been widely used in veterinary medicine, and other studies have reported a higher percentage of resistant isolates: 42.8% [82] and 28.9% [45]. On the contrary, our results show a relatively low percentage of non-susceptible isolates (12.4%).…”
Section: Antimicrobial Resistancecontrasting
confidence: 79%
“…Although performed on veterinary specimens, El-Razik et al found 50% of CoNS to have the tetK gene. 21 Moreover, 12 isolates that were positive for the tetK gene were sensitive to tetracycline. Duran et al too reported 15 staphylococcal isolates to be positive for tetK and tetM genes, but these isolates were phenotypically sensitive.…”
Section: Discussionmentioning
confidence: 99%